Liquid crystal based tunable terahertz metadevices - Lei Wang; Yanyan Wang; Guwei Zong; Wei Hu; Yanqing Lu (Journal of Materiomics)
Metasurface significantly enriches the light-matter interaction and promotes the development of planar optics. In recent years, with the rapid advancements of terahertz (THz) technology, THz devices with switchable and reconfigurable functions have been intensively pursued. Liquid crystal (LC), a unique soft matter that combines the fluidity of liquids and the order of crystals, is now indispensable in displays and spatial light modulations. LC is integrated with metasurfaces to realize dynamic THz devices and apparatuses as well. This review summarizes the research progress in LC based THz metadevices in three different respects: LC planar THz devices, LC integrated metal metasurfaces, and LC integrated dielectric metasurfaces. Various technologies for fabrications of LC microstructures and integrations of LCs with metal or dielectric metasurfaces are presented. The obtained LC metadevices exhibit excellent responsiveness to external stimulus such as electric fields, magnetic fields, heat, and light. By this means, the amplitude, frequency, phase as well as polarization of THz waves are dynamically manipulated. The LC based tunable THz metadevices will significantly improve THz applications in imaging, communication, and sensing.